2005
DOI: 10.1038/sj.eye.6702183
|View full text |Cite
|
Sign up to set email alerts
|

Deep sclerectomy with mitomycin C in failed trabeculectomy

Abstract: Aim To evaluate the success rate and complications associated with deep sclerectomy with mitomycin C (MMC) and a reticulated hyaluronic acid implant in previously failed trabeculectomy. Methods This prospective study included 20 eyes with a previously failed trabeculectomy, which were treated with deep sclerectomy with 0.2 mg/ml MMC application under the conjunctiva and superficial scleral flap. Intraocular pressure (IOP), glaucoma medications, visual acuity, and complications were recorded preoperatively and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…25 DS with MMC has been reported to be a safe and effective procedure for eyes with failed trabeculectomy. 26,27 There has been a lack of consensus among glaucoma surgeons as to the best surgical option in eyes at a high-risk-to-failure, such as previous intraocular surgery. The Tube versus Trabeculectomy (TVT) trial was designed to prospectively assess trabeculectomy and Bearveldt tube implant (BGI) surgery, both augmented with MMC, in eyes with previous cataract surgery and/or failed trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%
“…25 DS with MMC has been reported to be a safe and effective procedure for eyes with failed trabeculectomy. 26,27 There has been a lack of consensus among glaucoma surgeons as to the best surgical option in eyes at a high-risk-to-failure, such as previous intraocular surgery. The Tube versus Trabeculectomy (TVT) trial was designed to prospectively assess trabeculectomy and Bearveldt tube implant (BGI) surgery, both augmented with MMC, in eyes with previous cataract surgery and/or failed trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Most surgeons performing deep sclerectomy place a collagen or other implant 19,21,22,38–41 under the remaining superficial scleral flap to encourage subconjunctival drainage. With viscocanalostomy, on the other hand, Stegmann et al.…”
Section: Discussionmentioning
confidence: 99%
“…Rebolleda and Munoz‐Negerte in a study of deep sclerectomy with MMC in eyes with failed trabeculectomy (90% of which were pseudophakic) achieved a qualified success rate of 100% at 1‐year follow up without complications. They applied MMC under the conjunctival and superficial scleral flaps 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eyes that received MMC had significantly lower IOP and were less likely to require goniopuncture but also had a higher incidence of avascularized bleb and trans conjunctival oozing. Other prospective and retrospective studies have also reported the beneficial effect of antifibrotic agents on the final outcome of surgery [55][56][57].…”
Section: Antimetabolites: Mitomycin C and 5-fluorouracil As Antifibrotimentioning
confidence: 99%